Analisis Maintenance pada Mesin Forming Menggunakan Metode Reliability Centered Maintenance di PT. Refindo Intiselaras - Frastyansyah, Agun Syahrul; Muttaqin, Aan Zainal; Susanto, Doni (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research was conducted at PT. XYZ which is engaged in manufacturing, with a focus on forming machines. The purpose of this study was to analyze the maintenance system of forming machines using the Reliability Centered Maintenance (RCM) method, in order to improve machine reliability and reduce the frequency of damage. The results of the analysis showed that the bearing component had the highest RPN value of 224. The MTTF on the bearing machine was 312.39 hours. While the MTTR result was 213.2143. From these results, PT XYZ needs to conduct inspections about 1 month 2 times to increase the operational level of the forming machine, the addition of lubricants is also needed to reduce the frequency of failure in the bearing forming machine.